Risk, human rights and the management of a serious sex offender - Whitty, Noel (Lucius & Lucius, Stuttgart, 2007)
Risk and human rights discourses have become dominant features of the UK criminal justice arena. However, there has been little critical scrutiny of the ways in which these discourses relate to each other. In this article, I focus on different accounts of the case of Anthony Rice, a 48-year old ex-offender who committed a murder in August 2005 whilst under the joint supervision of English probation and police services. Drawing upon official reviews by the Inspectorate of Probation and the UK Parliament Joint Committee on Human Rights, as well as media coverage, I use the Rice case to problematise some common assumptions about the relationship between risk and human rights.